2015
DOI: 10.1111/bjd.13266
|View full text |Cite
|
Sign up to set email alerts
|

The role of the 595-nm pulsed dye laser in treating superficial basal cell carcinoma: outcome of a double-blind randomized placebo-controlled trial

Abstract: PDL is an effective and safe method for treating sBCC. However, the occurrence of persistent dyspigmentation still limits the potential for excellent cosmetic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…When comparing recurrence of low‐risk BCC post‐treatment with either PDL‐PDT or PDT alone, Carija et al found a higher recurrence rate in the combination arm which they postulated could be secondary to a reduction in photobleaching in PDL‐treated skin . A double‐blind randomized placebo‐controlled trial comparing PDL to placebo found a 78.6% complete remission in the PDL group, with a significant superiority demonstrated against placebo ( P < 0.0001).They did however note that pigmentary scarring was noted to be a limitation of this treatment . While there is evidence of PDL in some BCCs; current practice relates largely to small well‐defined superficial and/or nodular BCCs in low‐risk areas.…”
Section: Basal Cell Carcinomamentioning
confidence: 99%
“…When comparing recurrence of low‐risk BCC post‐treatment with either PDL‐PDT or PDT alone, Carija et al found a higher recurrence rate in the combination arm which they postulated could be secondary to a reduction in photobleaching in PDL‐treated skin . A double‐blind randomized placebo‐controlled trial comparing PDL to placebo found a 78.6% complete remission in the PDL group, with a significant superiority demonstrated against placebo ( P < 0.0001).They did however note that pigmentary scarring was noted to be a limitation of this treatment . While there is evidence of PDL in some BCCs; current practice relates largely to small well‐defined superficial and/or nodular BCCs in low‐risk areas.…”
Section: Basal Cell Carcinomamentioning
confidence: 99%
“…A 2015 study examined dye laser therapy prospectively. Tumor clearance was achieved in 78 % of sBCCs at low‐risk sites; however, there was frequent dyspigmentation . Clinical data is also available for the Nd:YAG laser (1,064 nm).…”
Section: Topical Treatmentmentioning
confidence: 99%
“…In einer 2015 veröffentlichten Studie wurde der Einsatz eines Farbstofflasers prospektiv untersucht. Hier konnten bei sBZK in Niedrigrisiko‐Lokalisationen in 78 % eine Tumorfreiheit erreicht werden, jedoch kam es regelmäßig zu Pigmentverschiebungen . Auch zum 1064 nm Nd:YAG‐Laser liegen klinische Daten vor.…”
Section: Topische Therapieunclassified